Hypermentalizing: the development and validation of a self-report measure - Sharp, Carla; Barr, C.; Vanwoerden, Salome (Frontiers in Psychology, 2025)
IntroductionHypermentalizing (referred to as excessive theory of mind or biased mindreading) is defined as the tendency to make assumptions about other people's mental states that go beyond observable data. Despite recent interest in this construct, no self-report measure of hypermentalizing exists. The aim of the current study was to fully operationalize the construct of hypermentalizing by developing a theoretically grounded (attachment-based) self-report measure of hypermentalizing assessing mentalizing related to parents, peers and intimate partners; and evaluate the new measure for its psychometric properties.MethodsIn Study 1,745 undergraduate students (mean age 21.12; SD = 2.19) completed the Hypermentalizing Questionnaire (HMZQ) alongside an experimental measure of mentalizing (the Movie Assessment for Social Cognition; MASC).ResultsResults of factor analyses with MASC scores for external validity confirmed the purported factor structure of the HMZQ and suggested superiority for the HMZQ version that assesses mentalizing in relation to parents. Study 2 compared HMZQ scores in 364 adolescents between 12 and 17 years of age (70 adolescents with BPD, 136 psychiatric controls, and 158 healthy controls), and confirmed the superiority of the 26-item version of the HMZQ that assesses mentalizing in relation to parents, in that it was only the HMZQ version that distinguished borderline personality disorder from other psychiatric disorders and healthy controls.DiscussionThe current study provides evidence in support of the HMZQ to assess hypermentalizing in typical and atypical populations of adolescents and young adults.